2011
DOI: 10.1248/jhs.57.171
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory and Antioxidant Effects of Aqueous Extract from Phellinus gilvus in Rats

Abstract: This study evaluated the antiinflammatory activities of an aqueous extract of Phellinus gilvus (PG) against carrageenan-and cotton pellet-induced acute and chronic inflammation in rats. Four acute and chronic inflammation groups included the vehicle control group, positive control group (aminopyrine, 100 mg/kg), PG10 group (PG, 10 mg/kg), and PG20 group (PG, 20 mg/kg). Oral administration of PG extract produced dose-dependent antiinflammatory effects in both the acute and chronic groups. In the carrageenan-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…At concentration of 1.6 mg/mL, the inhibitory percentage of n-Hexane fraction only reached 27.01%. A previous report showed similar result, DPPH radical scavenging activity of water fraction of P. gilvus collected in Korea was 55% at concentration of 0.1 mg/mL [29]. However, another report showed that ethyl acetate fraction of P. gilvus isolated in Korea had highest DPPH radical scavenging activity with IC50 value of 13.34 μg/mL (scavenging 70.38% of DPPH radical).…”
Section: Dpph Scavenging Activitymentioning
confidence: 63%
“…At concentration of 1.6 mg/mL, the inhibitory percentage of n-Hexane fraction only reached 27.01%. A previous report showed similar result, DPPH radical scavenging activity of water fraction of P. gilvus collected in Korea was 55% at concentration of 0.1 mg/mL [29]. However, another report showed that ethyl acetate fraction of P. gilvus isolated in Korea had highest DPPH radical scavenging activity with IC50 value of 13.34 μg/mL (scavenging 70.38% of DPPH radical).…”
Section: Dpph Scavenging Activitymentioning
confidence: 63%
“…The crude aqueous fruiting body extract of Phellinus showed anti-inflammation activity (IC 50 =19.46 µg/mL) on RAW 264.7 cells [48]. Furthermore, the ethanolic extract give 3,4-dihydroxybenzal-acetone (26) test with in acute lung injury (ICR mice) [29], igniaren B (35), igniaren D ( 36) and ergosta-6,22-die3 β -ol (37) exhibited anti-inflammatory activity test on RAW 264.7 cells with IC 50 values 5 mg/Kg mouse (In vivo), 47.89, 91.74 and 37.57 µg/mL, respectively [27,28] showed in Table 3.…”
Section: Anti-inflammatory Activitymentioning
confidence: 97%
“…Phytochemical compound of genus Phellinus has been reported to be rich sources of biological activities, reported that polysaccharides, flavones, coumarins, terpenes, steroids and styrylpyranones [8]. These compounds exhibit different bioactivities, such as anticancer [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], anti-inflammatory [27][28][29][30], antidiabetic [31], antioxidant [10,11,18,23,[32][33][34][35], antimicrobial [36][37][38][39][40][41][42][43] and hepatoprotective [11,37].…”
Section: List Of Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation